Azo dye removal by adsorption using waste biomass: sugarcane bagasse - Abdullah, Abdul Ghani Liew; Sobri, Shafreeza; Mustapa Kamal, Siti Mazlina; Mohd Salleh, Mohammad Amran; Megat Mohd Noor, Megat Johari; Osman, Mohd Rasid; Wagiran, Rahman (Federation of Engineering Institutions of Islamic Countries, 2006)
Dyes are usually present in trace quantities in the treated effluents of many industries. The effectiveness of adsorption for dye removal from wastewaters has made it an ideal alternative to other expensive treatment methods. This study investigates the potential use of sugarcane bagasse, pretreated with formaldehyde and sulphuric acid, for the removal of methyl red, an azo dye from simulated wastewater. The effects of condition such as adsorbent dosage, initial dye concentration, pH and contact time were studied. The results showed that as the amount of the adsorbent was increased, the percentage of dye removal increased accordingly. Higher adsorption percentages were observed at lower concentrations of methyl red. Sulphuric acid treated sugarcane baggase showed a better performance compared to formaldehyde treated sugarcane baggase, thus making it an interesting option for dye removal from dilute industrial effluents.